2023
DOI: 10.3390/rs15030772
|View full text |Cite
|
Sign up to set email alerts
|

Robust Single-Image Tree Diameter Estimation with Mobile Phones

Abstract: Ground-based forest inventories are reliable methods for forest carbon monitoring, reporting, and verification schemes and the cornerstone of forest ecology research. Recent work using LiDAR-equipped mobile phones to automate parts of the forest inventory process assumes that tree trunks are well-spaced and visually unoccluded, or else require manual intervention or offline processing to identify and measure tree trunks. In this paper, we designed an algorithm that exploits a low-cost smartphone LiDAR sensor t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 22 publications
2
8
0
Order By: Relevance
“…The greatest underprediction (−2.45 cm) occurred with Black Walnut trees. The overall RMSE (2.71 cm) was comparable to previous studies: Holcomb et al (2023) [14] reported an overall RMSE of 3.7 cm and a RMSE of 2.7 cm for trunks under 100 cm in diameter (all trunks in this study). Tatsumi et al (2022) [13] reported an RMSE of 2.27 cm using a LiDAR-enabled mobile phone and iPad, while Fan et al (2019) [10] reported an RMSE of 1.26 cm with an offline post-processing approach.…”
Section: Results Of Statistical Analysis and Species-level Analysissupporting
confidence: 89%
See 4 more Smart Citations
“…The greatest underprediction (−2.45 cm) occurred with Black Walnut trees. The overall RMSE (2.71 cm) was comparable to previous studies: Holcomb et al (2023) [14] reported an overall RMSE of 3.7 cm and a RMSE of 2.7 cm for trunks under 100 cm in diameter (all trunks in this study). Tatsumi et al (2022) [13] reported an RMSE of 2.27 cm using a LiDAR-enabled mobile phone and iPad, while Fan et al (2019) [10] reported an RMSE of 1.26 cm with an offline post-processing approach.…”
Section: Results Of Statistical Analysis and Species-level Analysissupporting
confidence: 89%
“…In general, diameter-estimation approaches can be performed in real-time (as the sampler is making the measurement) or via post-processing applied to images, point clouds, or other sensor data. Both hardware (e.g., [12]) and software (e.g., [13]) have been developed for this purpose, and various studies have sought to measure diameter in realtime (i.e., the user can view the measurement while they are still at the location of the tree, as in [14]), or via offline postprocessing algorithms to extract the diameter from images or other data after the user has left the location (e.g., [11]). Proudman et al (2022) [12] developed a handheld Light Detection and Ranging (LiDAR) unit to estimate tree diameters by modeling each tree trunk as a cylinder through a least-squares optimization within a Random Sample Consensus (RANSAC) loop, producing inventory results that can be viewed in the field, in ~1/4 the time of a traditional inventory.…”
Section: Background and Previous Workmentioning
confidence: 99%
See 3 more Smart Citations